The life and afterlife of gay neighborhoods: Renaissance and resurgence - Bitterman, Alex; Hess, Daniel Baldwin (Switzerland Springer Nature, 2021)
This open access book examines the significance of gay neighborhoods (or 'gayborhoods') from critical periods of formation during the gay liberation and freedom movements of the 1960s and 1970s, to proven durability through the HIV/AIDS pandemic during the 1980s and 1990s, to a mature plateau since 2000. The book provides a framework for contemplating the future form and function of gay neighborhoods.